2011
DOI: 10.1111/j.1460-9568.2011.07686.x
|View full text |Cite
|
Sign up to set email alerts
|

Differentiable contributions of human amygdalar subregions in the computations underlying reward and avoidance learning

Abstract: To understand how the human amygdala contributes to associative learning, it is necessary to differentiate the contributions of its subregions. However, major limitations in the techniques used for the acquisition and analysis of functional magnetic resonance imaging (fMRI) data have hitherto precluded segregation of function with the amygdala in humans. Here, we used high-resolution fMRI in combination with a region-of-interest-based normalization method to differentiate functionally the contributions of dist… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
46
0
2

Year Published

2011
2011
2018
2018

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 48 publications
(52 citation statements)
references
References 63 publications
4
46
0
2
Order By: Relevance
“…The BLA activity was found to be correlated extensively with temporal and frontal cortical regions whereas CMA predicted activity primarily in the striatum (Roy et al, 2009). A similar approach in generalized anxiety disorder (GAD) demonstrated differential connectivity of BLA and CMA (Etkin et al, 2009) and during reward and avoidance learning (Prevost et al, 2011). These initial results in humans demonstrate consistent, replicated delineation of differential connectivity of major amygdala complexes despite their small size and the limited spatial resolution of standard fMRI acquisitions.…”
Section: Introductionsupporting
confidence: 67%
“…The BLA activity was found to be correlated extensively with temporal and frontal cortical regions whereas CMA predicted activity primarily in the striatum (Roy et al, 2009). A similar approach in generalized anxiety disorder (GAD) demonstrated differential connectivity of BLA and CMA (Etkin et al, 2009) and during reward and avoidance learning (Prevost et al, 2011). These initial results in humans demonstrate consistent, replicated delineation of differential connectivity of major amygdala complexes despite their small size and the limited spatial resolution of standard fMRI acquisitions.…”
Section: Introductionsupporting
confidence: 67%
“…Our previous studies have indicated that free-operant avoidance behavior is affected by catecholamine manipulations of the NAcS, but not the NAc core subregion, suggesting some specificity of the NacS in avoidance behavior supported by appetitive-aversive interactions (Fernando et al, 2013c). Furthermore, connected regions of the NacS, such as the ventromedial prefrontal cortex and amygdala, have also been implicated in avoidance behavior, acting as interfaces for appetitive and aversive influences (Wilensky et al, 2000;Kim et al, 2006;Prévost et al, 2011;Moscarello and LeDoux, 2013;Fernando et al, 2013a). The dual role of the NacS in both appetitive and aversive processing suggests that the mechanism by which revaluation of the shock occurred with infusions of DAMGO differed between the NacS and PAG, with each region potentially mediating a different aspect of pain experience.…”
Section: Discussionmentioning
confidence: 99%
“…Human electrophysiological studies showed a dynamic interaction between the striatum and medial frontal cortex underlying reward-guided learning and decision-making (Cohen, 2007;Cohen et al, 2009). The amygdala was reported to facilitate reward-seeking behaviors by the glutamatergic or dopaminergic neurotransmission in the amygdala-striatum pathway (Lintas et al, 2011;Prevost et al, 2011;Stuber et al, 2011). Bilateral amygdala and nucleus accumbens showed significantly greater response to wins than to losses in both adolescents and adults (Ernst et al, 2005).…”
Section: Reward Dependencementioning
confidence: 99%